NtMYB4 and NtCHS1 Are Critical Factors in the Regulation of Flavonoid Biosynthesis and Are Involved in Salinity Responsiveness - Chen, Shuai; Wu, Fengyan; Li, Yiting; Qian, Yanli; Pan, Xuhao; Li, Fengxia; Wang, Yuanying; Wu, Zhenying; Fu, Chunxiang; Lin, Hao; Yang, Aiguo (Frontiers in plant science, 2019)
High levels of salinity induce serious oxidative damage in plants. Flavonoids, as antioxidants, have important roles in reactive oxygen species (ROS) scavenging. In the present study, the tobacco R2R3 MYB type repressor, NtMYB4, was isolated and characterized. The expression of was suppressed by salinity. Overexpression of reduced the salt tolerance in transgenic tobacco plants. NtMYB4 repressed the promoter activity of and negatively regulated its expression. Rutin accumulation was significantly decreased in overexpressing transgenic plants and RNAi silenced transgenic plants. Moreover, high H O and contents were detected in both types of rutin-reduced transgenic plants under high salt stress. In addition, exogenous rutin supplementation effectively scavenged ROS (H O and ) and improved the salt tolerance of the rutin-reduced transgenic plants. In contrast, overexpressing plants had increased rutin accumulation, lower H O and contents, and higher tolerance to salinity. These results suggested that tobacco NtMYB4 acts as a salinity response repressor and negatively regulates expression, which results in the reduced flavonoid accumulation and weakened ROS-scavenging ability under salt stress.